BORDER-BASED MANAGEMENT AT MADRASAH IBTIDAIYAH IN SEBATIK, NORTH KALIMANTAN - Santosa, Sedya; Kamala, Izzatin (UIN Sunan Kalijaga Yogyakarta, 2022)
Educational institutions have an essential role to play in dealing with border issues. Madrasah Ibtidaiyah Darul Furqon uses border issues to develop the governance of educational institutions. This research focuses on two things. First, what are the characteristics of border-based Islamic Elementary Education management at Madrasah Ibtidaiyah Darul Furqon? Second, how is the strength of the management in its participation in responding to border issues? Research with this qualitative method collects data through observation, interviews, and documentation. The analysis uses three stages: data reduction and presentation, and conclusion. This Madrasah has utilized school-based management to develop border-based Islamic Elementary Education Management. Among the characteristics of border issues concerning its management is branding as the Boundary School, the orientation of student recruitment by taking community groups with problems in border areas as its customer segments, and management of learning management based on border issues. The use of management like this gives strength to this Madrasah to manage aspects of the customer segment, value proposition, channel, key partnerships, key activities, and cost structure in the business management of educational institutions to deal with border issues. This Madrasah also utilizes management like this to develop inclusive Islamic religious education in the border context.